2007
DOI: 10.1002/cne.21606
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal cellular translocation of α‐internexin in spinal motor neurons of Dystonia musculorum mice

Abstract: Dystonia musculorum (dt) is a mutant mouse with hereditary neuropathy where the dysfunction is mainly found in the dorsal root ganglia (DRG) neurons but not in the spinal motor neurons. However, the accumulation of intermediate filament (IF) proteins in the swelling axons of spinal motor neurons could be found in dt/dt mice. In order to understand the pathological role of neuronal IFs in the swelling axons of spinal motor neurons from dt/dt mice, we extensively examined the distribution of neuronal IF proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
(77 reference statements)
2
11
0
Order By: Relevance
“…Chicken IgY anti-peripherin AB9282 (Millipore, Billerica, MA) was raised against recombinant peripherin protein and rabbit anti-peripherin AB1530 (Millipore, Billerica, MA) was raised against a trp-E fusion protein containing all but the four N-terminal amino acids. The rabbit anti-peripherin antibody has been previously characterized (Tseng et al , 2008), and the percentage of DRG neurons expressing peripherin was similar to other accounts (Table 1) (Goldstein et al , 1991). Double staining of DRG with both the chicken and rabbit antibodies revealed identical staining patterns.…”
Section: Methodssupporting
confidence: 72%
“…Chicken IgY anti-peripherin AB9282 (Millipore, Billerica, MA) was raised against recombinant peripherin protein and rabbit anti-peripherin AB1530 (Millipore, Billerica, MA) was raised against a trp-E fusion protein containing all but the four N-terminal amino acids. The rabbit anti-peripherin antibody has been previously characterized (Tseng et al , 2008), and the percentage of DRG neurons expressing peripherin was similar to other accounts (Table 1) (Goldstein et al , 1991). Double staining of DRG with both the chicken and rabbit antibodies revealed identical staining patterns.…”
Section: Methodssupporting
confidence: 72%
“…Lysates from cell lines transfected with the peripherin gene also showed a single band at approximately 58 kDa (Tseng et al, 2008; Xiao et al, 2008). Moreover, it was shown that the staining obtained with this antibody overlapped perfectly with that of eGFP-peripherin in PC12 cells (Tseng et al, 2008). As anticipated, this antibody produced filamentous staining of the neuronal perikarya in the nodose ganglion.…”
Section: Methodsmentioning
confidence: 99%
“…However, morphometric study has shown sensory innervations is significantly reduced in dt/dt mutants [3,5,7,8]. This study indicates that the sensory nerve is not only markedly denervated in the cutaneous part of footpads, but that sympathetic innervation is also severely impaired in sweat glands of young adult dt/dt mice.…”
Section: Discussionmentioning
confidence: 79%
“…Most previous studies on neuronal degeneration in dt/dt mice focused on the sensory nerve system [3,5], whereas the autonomic nervous system was seldom addressed. In our previous study of spinal motor neurons in dt/dt mice, no significant neuronal loss was observed in the spinal motor neurons [8]. However, the lifespan of these homozygous mutants is limited to three to four months.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation